Bisabolane sesquiterpene and cyclopentene derivatives from the marine algal-derived endophytic fungus Trichoderma asperellum EN-764. (June 2023) - Li, Hong-Lei; Li, Xiao-Ming; Ying, Zhen; Li, Yan-He; Wang, Bin-Gui
Abstract: Four undescribed bisabolane sesquiterpenes and one undescribed cyclopentene derivative, together with one undescribed naturally occurring cyclopentenone derivative, were isolated and identified from the culture of the endophytic fungus Trichoderma asperellum EN-764, which was obtained from the marine red alga Palisada papillosa . Their structures were determined by detailed interpretation of NMR and mass spectroscopic data, while the relative and absolute configurations were unambiguously established based on NOESY experiments, modified Mosher's method, X-ray diffraction, and quantum chemical calculations (ECD and DP4+ probability analysis). The antibacterial activities of the isolated compounds were evaluated, and they exhibited inhibitory activity against some aquatic pathogens with MIC values ranging from 4 to 64 μg/mL. Graphical abstract: Four undescribed bisabolene, one undescribed cyclopentene, and one undescribed naturally occurring cyclopentenone were isolated from the marine algal-derived fungus Trichoderma asperellum EN-764. Image 1 Highlights: Four undescribed bisabolanes and two undescribed cyclopentenes were isolated from marine fungus Trichoderma asperellum. The modified Mosher's method, X-ray diffraction, and quantum chemical calculations were applied to establish the stereochemistry. The bisabolanes showed inhibitory activity against aquatic pathogens with MIC values ranging from 4 to 64 μg/mL.